Prevalence of Placental Malaria Relative to Placental Cytokines and Birth Anthropometry Among Sub-Sahara Black African Women in their First or Second Pregnancy - Afolabi, Bamgboye M.; Okwuzu, Jane O.; Holdbrooke, Susan J.; Salako, Abideen; Ajibaye, Olusola; Aina, Oluwagbemiga O; Osinubi, Abraham A.; Raheem, Toyosi; Medubi, Leke J.; Enya, Veronica; et al. (British Journal of Healthcare and Medical Research, 2026)
Introduction: Pregnancy is a complex condition during which pathological complications such as iron deficiency anemia, infections, under- or over-nutrition and excessive production of cytokines may occur to jeopardize the well-being of the fetus. Objective: The objective of this study was to evaluate the interactions between placental or peripheral malaria (PlacMal or PerMal), Tumor Necrosis Factor-α (TNF-α), Interferon-γ (IFN-γ), Iron deficiency anemia (IDA), Platelets (Plt) and immature granulocytes (IG) in the placenta and neonatal birthweight, birth length and birth head circumference among study subjects in their 1st or 2nd pregnancy in Nigeria. Materials and Method: This was part of a prospective and exploratory study carried out among women in their 1st and 2nd pregnancy at Ikorodu General Hospital and its annex, Ita-Elewa Primary Health Care Center at Ikorodu, Lagos, Nigeria. Complete data from 78 women in their 1st or 2nd pregnancy who were assessed for TNF-α and IFN-γ, and whose socio-demographic characteristics, ante-natal history, birth anthropometry, placental hemogram and malaria parasitemia were recorded and analyzed. Data analysis was conducted using NCSS and STATA softwares. Results: Study participants in their 2nd pregnancy were significantly older (t-test=4.51, P-value=0.00004) and heavier (t-test=2.44, P-value=0.02) than those in their 1st pregnancy. While the means of TNF-α<20 pg/ml in subjects with (9.4±1.5) and without (20.3±24.1) PlacMal were notably different (t-test=3.74, P-value=0.0004), the means in subjects with (20.3±14.8) and without PerMal (19.8±25.4) were insignificant. At normal TNF of <20 pg/ml, mean birth length of neonates from 1st pregnancy (50.6±1.8 cm) was notable higher (t-test=2.98, P-value=0.005) than that those 2nd pregnancy (47.8±5.1 cm). Overall birthweight was significantly higher (3.2±0.5) when Hgb was ≥9.5 and TNF-α was <20 pg/ml than when Hgb was ≥9.5 and TNF-α was ≥20 pg/ml. Overall birth length (52.0±0.0) was notably longer (t-test=3.79, P-value=0.004) when IG was >0.456 and Hgb was <9.5 compared to when IG >0.456 and Hgb was ≥9.5. The mean platelets count (x109/L) of subjects with (27.7±14.2) and without (79.6±89.4) PlacMal were significantly different (t-test=3.94, P-value=0.002) but those of subjects with (69.2±50.5) and without (79.6±95.3) PerMal were not. Multivariate regression analysis indicates a positive, statistically significant relationship between birthweight and age group (coeff. = 0.22, SE=0.06, t-test = 3.78, P-value = 0.003). Conclusion: Placental TNF-α, IFN-γ, Platelet count, and IG may have a distinct or combined role to play the the development of gestation process and neonatal anthropometry. More studies are needed to support and substantiate these findings.